Identifikasi Tumbuhan Obat Tradisional di Kecamatan Seram Utara Barat Kabupaten Maluku Tengah - La Saita, Wiraldi; Kesaulya, Henry; Jambormias, Edizon (Jurnal Agrosilvopasture-Tech, 2023)
Inventorying and identifying plant species as ingredients for traditional medicines is very important because they have the potential to develop herbal medicines that have health and economic value. This study aims to identify various types of medicinal plants that are used by the community in the North West Seram District, Central Maluku Regency. Identified 13 species and 12 plant families consisting of Panadanaceae, Araceae, Acanthanthes, Annoaceae, Piperaceae, Aceanthaeae, Asteraceae, and Phyllantasheae. Lamiaceae, Poaceae, Zingiberaceae, and Garicaceae are used as traditional medicine. The Araceae family is most widely used as a traditional medicinal ingredient. Part of the leaf with a percentage of 59% is used by boiling as a traditional medicine.